Search and Investigation of Philosophical Base of the Theory of Strategy. Interrelation of Philosophical and Strategic Thinking - Vladimir Lvovich Kvint (Управленческое консультирование)
Fundamental philosophical bases of the theory of a strategizing are shown in the article. Based on the analysis of characteristics of philosophical and strategic thinking their deep intrinsic interrelation generating a phenomenon of strategic consciousness is proved. Opportunity, necessity and ways of formation of strategic thinking for the purpose of increase of management efficiency, development of optimum tactics and practical actions is proved.